Pre-linguistic Vocal Trajectories at 6–18 Months of Age As Early Markers of Autism - Chericoni, Natasha; de Brito Wanderley, Daniele; Costanzo, Valeria; Diniz-Gonçalves, Andréa; Leitgel Gille, Marluce; Parlato, Erika; Cohen, David; Apicella, Fabio; Calderoni, Sara; Muratori, Filippo (Frontiers in Psychology, 2016)
This study explores pre-linguistic vocal trajectories in infants with autism spectrum disorder (ASD) during caregiver-infant interaction. Home videos were obtained from 10 infants with ASD and 10 typically developing infants (TD), covering three time periods: 0-6 months (T1, 47 video sequences), 6-12 months (T2, 47 video sequences), and 12-18 months (T3, 48 video sequences). In total 142 video sequences were analyzed. Vocalizations, long reduplicated babbling, 2-syllable babbling, and first words were investigated longitudinally. Face-gazing was also analyzed, to evaluate the social quality of vocal behaviors. Results show a lower rate of vocalizations in the ASD group at T2, and a lower rate of first words at T3, compared to the TD group. However, the prevalence of non-social babbling, appeared higher in the ASD group. The implications of these findings for screening programs are discussed.